Solid-state acidochromic properties of barbituric acid-based 1, 4-dihydropyridine derivatives with multiple coloured emissions switching. (January 2019) - Wang, Mengzhu; Qian, Lebin; Guo, Yang; Wu, Huayue; Liu, Miaochang; Gao, Wenxia; Li, Guoxing; Ding, Jinchang; Huang, Xiaobo
Abstract: Solid-state acidochromic (SSAC) molecules often exhibit dual-coloured rather than multi-coloured stimuli-responsive properties. To obtain the molecule possessing a multi-coloured emission switching based on one specific solid-state of a single molecule, a new D-π-A type 1, 4-dihydropyridine derivative 4a containing barbituric acid and N, N -dimethylaniline unit, which contains multiple sites that can be combined with H +, is designed and synthesized. Compound 4a is confirmed to have twisted molecular conformation by crystallographic data and exhibits aggregation-induced emission characteristic. Upon the stimuli of acid-base system, 4a exhibits rare seven-coloured emission switching in solid-state. Another 1, 4-dihydropyridine derivative 4b based on 1, 3-dimethylbarbituric acid is synthesized for comparison. Compared with 4b which only displays three-coloured solid-state emission switching, 4a exhibits a more abundant colour change, which might be attributed that the nitrogen atoms on the NH bonds are also involved in the process of protonation and deprotonation, slowing down the transformation between D-π-A and A-π-A structures. The results provide a new idea for the development of multicolour SSAC materials. Graphical abstract: Image 1 Highlights: Synthesis and characterization of two new 1, 4-dihydropyridine derivatives. These AIE-active compounds exhibit solid-state acidochromism. Barbituric acid-based compound shows rare seven-coloured emission switching in solid-state.